Concentration‐QTc and cardiac safety analysis of single and multiple zavegepant nasal spray doses in healthy participants to support approval - Jim H. Hughes; Richard Bertz; Rajinder Bhardwaj; Mary K. Donohue; Jennifer Madonia; Matt S. Anderson; Beth A. Morris; Robert S. Croop; Jing Liu (Wiley, 2024)
Abstract Zavegepant is a novel gepant administered as a nasal spray approved in the United States at a 10 mg dose for the acute treatment of migraine with or without aura in adults. The cardiovascular safety of zavegepant nasal spray was assessed in both single‐ascending dose (SAD) and multiple‐ascending dose (MAD) studies in healthy participants. The SAD study included 72 participants (54 active/18 placebo) who received 0.1-40 mg zavegepant or placebo. The MAD study included 72 participants (56 active/16 placebo) who received 5-40 mg zavegepant or placebo for 1-14 days. Plasma zavegepant pharmacokinetics and electrocardiographic (ECG) parameters (Fridericia‐corrected QT interval [QTcF], heart rate, PR interval, ventricular depolarization [QRS], T‐wave morphology, and U‐wave presence) were analyzed pre‐ and post‐zavegepant administration. Using pooled data from the SAD and MAD studies, the relationship between time‐matched plasma zavegepant concentrations and QTc interval was assessed using a linear mixed‐effects model to evaluate the potential for QTc interval prolongation. Results showed that single and multiple doses of zavegepant had no significant impact on ECG parameters versus placebo, and there was no concentration‐dependent effect on QTcF interval. The estimated slope of the plasma zavegepant concentration‐QTcF model was −0.053 ms per ng/mL with a 90% confidence interval of −0.0955 to −0.0110 (p = 0.0415), which is not considered clinically meaningful. At doses up to four times the recommended daily dose, zavegepant does not prolong the QT interval to any clinically relevant extent.